The efficacy and safety of Chinese traditional medicine injections on patients with coronavirus disease 2019: A protocol for systematic review and meta analysis. Issue 31 (31st July 2020) - Li, Yulin; Xu, Haonan; Lang, Hui; Li, Jing; Bi, Lin; Li, Yanqing; Dong, Liang; Zhang, Lin; Liang, Xin; Zhu, Hongqiu
Abstract: Introduction: The pandemic caused by the coronavirus disease 2019 (COVID-19) infection has exposed vulnerable populations to an unprecedented global health crisis. Research reported that Chinese traditional medicine injections were used in patients with COVID-19 infection and showed significant effects, and there have been no systematic review and meta-analyses to investigate the effects and safety of Chinese traditional medicine injections. Materials and methods: This systematic review and meta-analysis protocol is based on the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols 2015 statement. The literature search will involve Cochran library, Web of science, PubMed, MEDLINE, Embase, China Biology Medicine Database, China National Knowledge Infrastructure Database, VIP, Wang Fang database, and China Clinical Trial Registration Center for articles and research published form December 2019. This search will include randomized controlled trials and nonrandomized studies. The Cochrane Collaboration's tool for randomized controlled trial studies and the Quality Assessment Tool for Quantitative Studies for nonrandomized studies will be used to assess the risk of bias among the studies included in the systematic review. Review Manager 5.3 software will be used for the meta-analysis, and odds ratio are calculated as the primary outcomes. Subgroup analyses will then be performed based on the characteristics of the interventions and populations included in the studies examined. Ethics and dissemination: This systematic review protocol is designed to provide evidence regarding the effects and safety of Chinese traditional medicine injections on patients with COVID-19, such evidence may be useful and important for clinical treatment decisions. The results should be disseminated through publication in a peer-reviewed journal. Since the data and results used in the systematic review will be extracted exclusively from published studies, approval from an ethics committee will not be required.